2005
DOI: 10.1017/s1743921305006794
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid-meteorite links: the Vesta conundrum(s)

Abstract: Abstract. Although a direct link between the HED meteorites and the asteroid 4 Vesta is generally acknowledged, several issues continue to be actively examined that tie Vesta to early processes in the solar system. Vesta is no longer the only basaltic asteroid in the Main belt. In addition to the Vestoids of the Vesta family, the small asteroid Magnya is basaltic but appears to be unrelated to Vesta. Similarly, diversity now identified in the collection of basaltic meteorites requires more than one basaltic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…3) that exhibit similar but stronger diagnostic mineral absorption bands. The strength of the bands observed for the Vestoids are much closer to that observed in laboratory studies of meteorites (Binzel and Xu 1993;Hiroi et al 1995;Pieters et al 2006). Marchi et al (2010), Moskovitz et al (2010), andDe Sanctis et al (2011b) investigated several of the small Vestoids using earth-based telescopes and found that their visible slopes are generally redder than that of Vesta and systematically redder than HEDs measured in the laboratory.…”
Section: Spwe: Dawn Science Objectivessupporting
confidence: 76%
See 1 more Smart Citation
“…3) that exhibit similar but stronger diagnostic mineral absorption bands. The strength of the bands observed for the Vestoids are much closer to that observed in laboratory studies of meteorites (Binzel and Xu 1993;Hiroi et al 1995;Pieters et al 2006). Marchi et al (2010), Moskovitz et al (2010), andDe Sanctis et al (2011b) investigated several of the small Vestoids using earth-based telescopes and found that their visible slopes are generally redder than that of Vesta and systematically redder than HEDs measured in the laboratory.…”
Section: Spwe: Dawn Science Objectivessupporting
confidence: 76%
“…A general review of telescopic measurements of Vesta and its relation to HED meteorites can be found in Pieters et al (2006). As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most firmly established asteroid-meteorite link is between the HED meteorites (howardites, eucrites, and diogenites) and the asteroid (4) Vesta and its family (Pieters et al 2006). The fragments from the cratering on Vesta occupy the space up to the 3:1 resonance with Jupiter, which is the dynamical gateway to deliver bodies from the main belt to Earth-crossing orbits.…”
Section: Asteroids As Potential Parent Bodiesmentioning
confidence: 99%
“…30-40 in eucrites) showing that it probably comes from a separate parent body Floss et al, 2005). Although Vesta appears to be the only intact basaltic asteroid (Pieters et al, 2005), there are many smaller asteroids (≤30 km across) with reflectance spectra like those of Vesta (called V-types) that have orbits outside Vesta's family (e.g., Lazzaro et al, 2000;Moskovitz et al, 2008). One of the V-type asteroids that lies beyond the 3:1 resonance marking the outer edge of the Vesta family, such as 1459 Magnya, may have been the source of NWA 011.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the igneous processes that generated eucrites and diogenites (Mittlefehldt, 2007), but cooling of a magma ocean appears to provide a more comprehensive explanation for the diverse lithologies than partial melting (Righter and Drake, 1997;Ruzicka et al, 1997). Spectrometric studies of meteorites and asteroids strongly suggest that HEDs are derived from Vesta, the third largest asteroid, and its family of sub-10 km diameter asteroids (Drake, 2001;Pieters et al, 2005).…”
Section: Introductionmentioning
confidence: 99%